Beta diversity along an elevational gradient at the pico da neblina (Brazil): Is spider (arachnida-araneae) community composition congruent with the guayana region elevational zonation? - Nogueira, André A. [UNESP]; Brescovit, Antonio D.; Perbiche-Neves, Gilmar [UNESP]; Venticinque, Eduardo M. (MDPI, 2021)
Beta diversity is usually high along elevational gradients. We studied a spider community at the Pico da Neblina (Brazil), an Amazonian mountain which is one of the southern components of the Guayana region. We sampled six elevations and investigated if beta diversity patterns correspond to the elevational division proposed for the region, between lowlands (up to 500 m), uplands (500 m to 1500 m), and highlands (>1500 m). Patterns of dominance increased with elevation along the gradient, especially at the two highest elevations, indicating that changes in composition may be accompanied by changes in species abundance distribution. Beta diversity recorded was very high, but the pattern observed was not in accordance with the elevationaldivision proposed for the region. While the highlands indeed harbored different fauna, the three lowest elevationshad similar species compositions, indicating that the lowlands spider community extends into the uplands zone. Other measures of compositional change, such as similarity indices and species indicator analysis, also support this pattern. Our results, in addition to a revision of the literature, confirm the high diversity and endemism rates of montane spider communities, and we stress the importance of protecting those environments, especially considering the climate crisis.
Keywords: Arachnida; Araneae; Biodiversity; Community ecology; Elevation; Pantepui; Species turnover